Knowledge, attitude and practice of physicians towards oral anti-coagulants in Taif city, Saudi Arabia - Alnemari, Raghad; Banheem, Ahmed; Mullaniazee, Naeem; Alghamdi, Saleh; Rajkhan, Abdulmajeed; Basfar, Omar; Basnawi, Mohammed (International Journal of Advances in Medicine, 2018)
Background: Thromboembolism is a common phenomenon of major significance. Oral anticoagulants have been used for decades, however, they were associated with many complications and different monitoring techniques. Therefore, novel oral anticoagulants (NOACs) with better efficacy, lower adverse events, superior pharmacokinetic and pharmacodynamic profile were developed. Unfortunately, many of the physicians are still hesitant to prescribe these agents. Methods: This was a cross-sectional study conducted in Taif city on 61 physicians from King Abdulaziz Specialist Hospital and King Faisal Hospital in Taif. A questionnaire was given to participants to answer questions related to knowledge, attitude, and practice of prescription of KA and NOACs, indications of prescription, reasons for non-use, follow up methods adopted, follow up frequency, common adverse events encountered, awareness of new guidelines of NOACs, and providing patients with health education about their medications. Results: Only 69% of participants used NOACs on regular basis, whilst 100% used warfarin. Half of those who didn't prescribe NOACs attributed this to the non-availability of an antidote and fear of toxicity. Twenty-five% considered the NOACs new medications with inadequate clinical trials that make them trustable., and 17% did not prescribe them because of their non-availability at the hospital pharmacy. Only 66% used NOACs in treatment of non-valvular atrial fibrillation. Regarding knowledge, 71% of participants were aware of the new guidelines of NOACs, and 69% of institutions provided educational programs about these new agents. Major life-threatening bleeding was reported in 47.3% and 10.8% of patients on warfarin and NOACs, respectively. Conclusions: Physicians at Taif city in Saudi Arabia had a fairly good knowledge of NOACs. They prescribed them frequently and they were aware with the new guidelines and proper follow-up methods. However, more educational activities are recommended to encourage the rest of physician to use these agents and to correct their defective information about safety issues, pharmacokinetic and pharmacodynamic properties of NOACs, and adverse events.